Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1620/tjem.241.35
|View full text |Cite
|
Sign up to set email alerts
|

Expression of (Pro)renin Receptor During Rapamycin-Induced Erythropoiesis in K562 Erythroleukemia Cells and Its Possible Dual Actions on Erythropoiesis

Abstract: (Pro)renin receptor ((P)RR), a specific receptor for renin and prorenin, is expressed in erythroblastic cells. (P)RR has multiple biological actions: prorenin activation, stimulation of the intracellular signaling including extracellular signal-regulated kinases, and functional complex formation with vacuolar H + -ATPase (v-ATPase). However, the functional implication of (P)RR in erythroblast cells has not been clarified. The aim of the present study was to clarify changes of (P)RR expression during erythropoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
(54 reference statements)
2
4
0
Order By: Relevance
“…The results further studies confirm the thesis that the system (pro) renin -(pro) renin receptor has an important function in pathogenesis and progression of cancer (Shibayama Y. et al, 2015;Wang C. et al, 2016;Kaneko K. et al, 2017). No less relevant is the importance of information systems (pro) renin -(pro) renin receptor in the control of gene expression, regardless of the state PAC activity (Nguyen G., 2011;Müller DN et al, 2012.).…”
Section: Epigenetic Mechanisms As Possible Regulators Expression Of Tsupporting
confidence: 81%
“…The results further studies confirm the thesis that the system (pro) renin -(pro) renin receptor has an important function in pathogenesis and progression of cancer (Shibayama Y. et al, 2015;Wang C. et al, 2016;Kaneko K. et al, 2017). No less relevant is the importance of information systems (pro) renin -(pro) renin receptor in the control of gene expression, regardless of the state PAC activity (Nguyen G., 2011;Müller DN et al, 2012.).…”
Section: Epigenetic Mechanisms As Possible Regulators Expression Of Tsupporting
confidence: 81%
“…No less relevant is the importance of the (pro)renin-(pro)renin receptor information systems in the control of gene expression, regardless of the state of RAS activity ( 52 , 53 ). The results of other studies confirm the thesis that the (pro)renin-(pro)renin receptor system has an important function in cancer pathogenesis and progression ( 54 , 69 , 70 , 72 , 73 ).…”
Section: Diagnostic Value Of Ras Protein Components In Oncologysupporting
confidence: 79%
“… 16 It is noteworthy that recent studies have identified the expression of prorenin receptor (pRR), a specific receptor for renin and prorenin, in erythroid cells. 17 , 18 Overexpression of pRR leads to partial negative regulation of erythropoiesis in chronic inflammation. 5 Therefore, we speculate that the extremely low levels of PRA in anephric patients may lead to an insufficient combination of pRR on erythroid cells with renin, contributing to the amelioration of anemia, but the exact conclusion requires further study.…”
Section: Discussionmentioning
confidence: 99%